2011
DOI: 10.1101/cshperspect.a009712
|View full text |Cite
|
Sign up to set email alerts
|

The Thrombospondins

Abstract: Thrombospondins are evolutionarily conserved, calcium-binding glycoproteins that undergo transient or longer-term interactions with other extracellular matrix components. They share properties with other matrix molecules, cytokines, adaptor proteins, and chaperones, modulate the organization of collagen fibrils, and bind and localize an array of growth factors or proteases. At cell surfaces, interactions with an array of receptors activate celldependent signaling and phenotypic outcomes. Through these dynamic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
416
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(432 citation statements)
references
References 155 publications
8
416
0
Order By: Relevance
“…We also report VEGF levels in platelets of normal individuals to be 0.74 ± 0.37 pg/10 6 platelets (range 0.15-1.86), values very similar to those reported by Salven et al [27] [0.5 pg/10 6 platelets (range 0.1-1.6)]. The levels of TSP-1 in plasma have been described as 180 ng/mL [28], which was lower than those determined in our studies (559 ± 272 ng/mL). We found no direct measurements of TSP-1 in platelets in the literature.…”
Section: Discussionsupporting
confidence: 70%
“…We also report VEGF levels in platelets of normal individuals to be 0.74 ± 0.37 pg/10 6 platelets (range 0.15-1.86), values very similar to those reported by Salven et al [27] [0.5 pg/10 6 platelets (range 0.1-1.6)]. The levels of TSP-1 in plasma have been described as 180 ng/mL [28], which was lower than those determined in our studies (559 ± 272 ng/mL). We found no direct measurements of TSP-1 in platelets in the literature.…”
Section: Discussionsupporting
confidence: 70%
“…Its expression is highly regulated by different hormones and cytokines, and is developmentally controlled (16). The levels of TSPs in body fluids and their distribution in tissues have been correlated with various pathological states (17). TSP-1 is transiently expressed at high concentrations in damaged and inflamed tissues.…”
Section: B Acterial Meningitis Is the Most Common And Devastating Infmentioning
confidence: 99%
“…Previously, we had found that two genes encoding axolotl thrombospondins, thrombospondin-1 (tsp-1) and thrombospondin-4 (tsp-4), displayed dynamic expression patterns in discrete cell types during the course of limb regeneration (32). Although thrombospondins have been implicated in numerous aspects of mammalian biology (33), including some that may be pertinent to regeneration such as wound healing and angiogenesis, nothing is known about their potential role in appendage regeneration.…”
Section: Testing the Ability Of Various Inducible Genetic Systems Tomentioning
confidence: 99%